The Role of Social Media Adoption and Dynamic Capabilities to Boost SMEs Performance: A Moderated Analysis - Uce Karna Suganda; Tuti Asmala; M. Dana Prihadi (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2022)
The objective of this study is to examine and analyze the direct influence of social media adoption and dynamic capabilities in increasing SMEs performance. It also considers market orientation as a moderating variable to understand more about the condition by which the relationship between the variables can be strengthened or weakened. By using quantitative approach, this study focuses on culinary SMEs in Bandung, West Java. The number of samples is 300 respondents, and the data is collected through giving questionnaire using Google Forms to culinary SMEs actors. The findings of this study indicate that both social media adoption and dynamic capabilities have a positive influence on SMEs performance. Furthermore, this study also prove that market orientation can strengthen the relationship between social media adoption and SMEs performance, as well as dynamic capabilities and SMEs performance. Finally, several implications are pointed out for both practitioners and scholars.